1994
DOI: 10.1016/0014-5793(94)01035-8
|View full text |Cite
|
Sign up to set email alerts
|

Olomoucine, an inhibitor of the cdc2/cdk2 kinases activity, blocks plant cells at the G1 to S and G2 to M cell cycle transitions

Abstract: The cdc2/cdk2 protein kinases play key roles in the cell cycle at two control points: the G1/S transition and the entry into mitosis. Olomoucine, a specific inhibitor of these kinases, was tested in two plant cell systems: Petunia mesophyll protoplasts induced to divide and Arabidopsis thaliana cell suspension cultures. The cell cycle status was analysed from DNA histograms or through continuous labelling of cells with 5-bromodeoxyuridine (BrdUrd) followed by double staining with bis-benzimide (Hoechst 33258) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 24 publications
4
93
0
Order By: Relevance
“…In contrast, Cdk2-speci®c chemical inhibitors, olomoucine and roscovitine (Glab et al, 1994;Vesely et al, 1994;Schulze-Gahmen et al, 1995), decreased cyclin D2-associated kinase activity but had little eect on cyclin D1-associated kinase assays performed in parallel (Figure 2b and c). As expected, the general CDK-inhibitor p21 (WAF1, CIP1, Harper et al, 1993;Xiong et al, 1993) signi®cantly inhibited both cyclin D1-and D2-associated kinase activity (Figure 2b and c).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, Cdk2-speci®c chemical inhibitors, olomoucine and roscovitine (Glab et al, 1994;Vesely et al, 1994;Schulze-Gahmen et al, 1995), decreased cyclin D2-associated kinase activity but had little eect on cyclin D1-associated kinase assays performed in parallel (Figure 2b and c). As expected, the general CDK-inhibitor p21 (WAF1, CIP1, Harper et al, 1993;Xiong et al, 1993) signi®cantly inhibited both cyclin D1-and D2-associated kinase activity (Figure 2b and c).…”
Section: Resultsmentioning
confidence: 96%
“…Several lines of evidence support this conclusion: the Cdk4/Cdk6-speci®c physical inhibitor p16 (Serrano et al, 1993) had little or no eect on the cyclin D2-associated kinase activity while the Cdk2-speci®c chemical inhibitors, roscovitine and olomoucine (Glab et al, 1994;Vesely et al, 1994;Schulze-Gahmen et al, 1995) did block the kinase activity. Finally, cyclin D2 immunocomplexes phosphorylated histone H1 (Figures 2b and 5b), a substrate that is not phosphorylated by Cdk4 or Cdk6 (Matsushime et al, 1994;Meyerson and Harlow, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…Analysis of CDK2/olomoucine crystals showed that the purine group of olomoucine is located in the pocket where ATP binds to CDK2 [35]. In vivo, olomoucine blocks plant cells at the G1/S and G2/M transitions [36]. Thus, according to this hypothesis, the general structure of the molecule (a specific cytokinin or a synthetic analogue such as olomoucine) may determine its specificity to certain CDK-cyclin complexes, or to other kinases, such as MAP kinases or the kinases that regulate CDK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Suspensions of cultured cells of A. thaliana (L.) Heynh. (ecotype Columbia-0) were maintained as described (37). For elicitation, a 7-day-old culture was diluted 10-fold in fresh medium and grown for 16 h. Subsequently, MeJA (Duchefa) at a final concentration of 50 M or an equal volume of solvent (DMSO) was added to the cultures.…”
Section: Methodsmentioning
confidence: 99%